2020
DOI: 10.34172/jlms.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Therapeutic Effect of Low Level Laser in Controlling Low Back Pain: A Randomized Controlled Trial

Abstract: Introduction: Low back pain (LBP) is a very common musculoskeletal disorder. The big burden of disease necessitates investigating a more effective modality of treatments with more persistence and also fewer side effects. Low power laser has been proved as a pain reducing modality, but there is a lack of studies comparing it with other treatments and also among the Iranian race and society. The purpose of this study was to evaluate the effect of low-level laser on patients with LBP. Methods: Our study was a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…HILT is a therapy used in isolation and in combination with other thermotherapy and electrotherapy procedures [ 125 , 126 ]. Moreover, in most cases, it is used in conjunction with physical therapy, playing an essential role in modulating pain [ 127 ].…”
Section: Manual Therapy–tecar–hilt Therapy: Methods Of Use In the Tre...mentioning
confidence: 99%
“…HILT is a therapy used in isolation and in combination with other thermotherapy and electrotherapy procedures [ 125 , 126 ]. Moreover, in most cases, it is used in conjunction with physical therapy, playing an essential role in modulating pain [ 127 ].…”
Section: Manual Therapy–tecar–hilt Therapy: Methods Of Use In the Tre...mentioning
confidence: 99%
“…Finally, 20 articles were included, comprising 568 patients receiving LA and 534 patients receiving sham treatment. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] The process of study search, screening, and selection is shown in Figure 1, and the characteristics of included articles are described in Table 1. The risk of bias of each included study is depicted in Supplementary Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The laser can reduce this pain. According to Kholoosy et al (2020) Although the effect of dry needling is primarily inhibition of pain at the synapse (Sprouse-Blum et al, 2010) and metabolism (Cagnie et al, 2013), while the laser is from the field of collagen proliferation, anti-inflammatory effects, increased circulation, and peripheral nerve stimulation (Clijsen et al, 2017) and metabolism (Heu et al, 2013). Also, both research groups received the myofascial release, and both had a relaxing effect (Boyajian-O'Neill and Cardone, 2008) and improved metabolism (Moraska et al, 2013).…”
Section: Resultsmentioning
confidence: 99%